How Asian slum emissions impact local microclimates in polluted air masses. (30th July 2022) - Ghosh, Satyajit; Sathish Kumar, C. R.; Gumber, Siddharth; Dobbie, Steven; Yang, Huiyi
Abstract: Urban sprawl comprising densely populated slums over South Asian cities yields copious amounts of soot and black carbon from archaic cooking methods involving cow dung cakes and firewood, which remain afloat for over 10–12 h, enabling them to age in a sulphur rich environment. Not only are there toxicological concerns arising out of improper ventilation mechanisms, but there are also other concerns impacting the local microclimate. These emissions mix with other aerosol particles and, when conditions are favourable, are rendered partially soluble, enabling them to activate into cloud condensation nuclei. This study first yields a quantification of the soluble mass fraction and subsequently shows how aerosols from this local area source mix with background aerosol modes to perturb the local cloud microphysics over Chennai, a megacity in Southern India. On‐site sampling was undertaken to find the mass concentrations of the collected deposits separately from cow dung and firewood fuel. Additional micro‐physical attributes, including the morphological indentations that served as a receptacle to contain the accreted sulphate along with the particle size distribution were ascertained through Scanning Electron Microscopy. It is shown that accreted sulphate on carbonaceous particles facilitates CCN activation over the city. We show through large‐eddy simulations (LES) that extensive slum emissions over the study region contribute to the observed local cloud cover and enhanced rain amounts over a densely built‐up area housing the city's most vulnerable citizens. Abstract : Cook stove emissions over urban sprawl in South India and expected microphysical implications. Combustion‐mediated soot and black carbon from biomass burning in shantytowns modulate the local cloud cover.